Fruit yield and quality of wild passion fruit cultivars - Kelli de Oliveira, Marines; Ramos Cavalcante, Natan; Azevedo Santos, Eileen; Alexandre Silva, Celice; Castro Silva, Dayane; Krause, Willian (Comunicata Scientiae, 2025)
Wild Passiflora species have considerable economic potential; however, they remain underexplored due to limited research. This study evaluated productive and physicochemical parameters of four passion fruit cultivars—Roxinho (Passiflora edulis), BRS Mel do Cerrado (P. alata), BRS Pérola do Cerrado (P. setacea), and BRS Sertão Forte (P. cincinnata)—and assessed fruit yield and quality throughout the annual cycle. The experiment was conducted at the Mato Grosso State University (UNEMAT), Tangará da Serra, Mato Grosso, Brazil, using a randomized complete block design with five replications and five plants per plot. The variables measured were fruit yield, number of fruits, fruit mass, fruit length, fruit diameter, peel thickness, pulp percentage, fruit shape index, total soluble solids (TSS), titratable acidity (TA), the TSS-to-TA ratio, and pH. Significant differences were observed among cultivars for all variables except pH. Roxinho showed the highest fruit yield (18,653.41 kg ha−1), whereas BRS Mel do Cerrado exhibited the highest fruit mass (184.74 g) and TSS (20.25 ºBrix), but the lowest pulp percentage. BRS Sertão Forte exhibited the highest TA and yield stability, which are desirable characteristics for industrial processing. Thus, diversified cultivation of wild passion fruit species may be an efficient strategy to reduce production seasonality throughout the year and meet the demands of different market segments.